(untitled) (Biological Sciences - PJSIR, 1994)
Halogenation of 4. 7-dihydroxy-I, 1O-phenanthrolin-2. 9-dione has been studied using different halogenating agents under different conditions. The halo compounds so obtained were reacted with some chemical reagents, with the purpose of establishing their compositions. The structures of all the newly obtained compounds were confirmed by elemental analysis. IR and lH-NMR spectroscopic studies.